Outdoor Adventure Education Trends and New Directions - Roberts, Nina S. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The overall focus, scope, and purpose of this Special Issue on outdoor adventure is to provide the current and anticipated future trends, offer innovative ideas for new programs, support decision making for managers to move plans and intentions into action, inspire pioneering staff training and leadership development, incite policy reviews and revisions, promote resource (re)allocation where needed, and stimulate culture shifts among outdoor leaders and managers. Furthermore, this Special Issue is situated within the existing literature by depicting major trends in the field, exploring organizational issues and successes, identifying gaps between research and practice, and formulating solutions to some of the field's most pressing challenges. Of particular interest were manuscripts reporting the following: • Adventure education across diverse cultures; • Innovative partnerships for experiential education outdoors; • Land management agencies working with adventure education programs; • Leadership and/or management issues and challenges; • Programming advances, participation trends; • Recruitment and retention of diverse staff, workforce enhancement; • Social groups/identity and outdoor spaces (e.g., people of color and outdoor adventure; women in the outdoors-where have we been, where are we going?; LGBTQ trends and future directions; youth and outdoor adventure); • Socioeconomic factors and solutions; • Technology influences and adventure education; • Working with schools/school districts and being in sync with curriculum needs, supporting transportation challenges, etc.